Développement de paramètres physiologiques, anthropométriques et psychologiques durant l`adolescence au hockey sur glace - Huard Pelletier, V.; Trudeau, F.; Lemoyne, J. (Movement & Sport Sciences - Science & Motricité, 2025)
Purpose: One of the most critical periods in a player`s development is adolescence when major competitions and hormonal changes occur. However, very few studies have investigated ice hockey-related performances during this period and whether players` perceptions of competence also evolve. Therefore, this study aimed to measure the progression of players` different anthropometric, physiological, and psychological attributes as a function of their pubertal status and team selection during a competitive ice hockey season.